Effects of Group Counseling Sessions on Perceived Stress Among Undergraduate Students During COVID19 Pandemic - Amalia Madihie; Vanedda Antek Jalik (Educational Guidance and Counseling Development Journal, 2022)
This study was aimed to assess the pre-test and post-test effects of group counseling sessions on perceived stress among undergraduate students during the COVID-19 pandemic. This study was inspired by the fact of the impact of COVID-19 pandemic on students' well-being during the pandemic. A true experiment design pretest posttest control group was employed in this study. Through purposive sampling, a total of 30 counseling students from a local university has been selected as representative of the sample population. Perceived-Stress Scale has been measured at pre and posttest.   The results showed there are differences between the pre-test and post-test results after the experiment has been conducted by the researcher. This study provided valuable information about the appropriate intervention that can be used in order to cope with the group counseling session on perceived stress among undergraduate students during the COVID-19 pandemic. Thus, students should be introduced early to the university counselling services so that they can learn about the knowledge and techniques of coping with stress issues